Development and validation of an artificial intelligence based screening tool for detection of retinopathy of prematurity in a South Indian population - Rao, Divya Parthasarathy; Savoy, Florian M.; Tan, Joshua Zhi En; Fung, Brian Pei-En; Bopitiya, Chiran Mandula; Sivaraman, Anand; Vinekar, Anand (Frontiers in Pediatrics, 2023)
Purpose: The primary objective of this study was to develop and validate an AI algorithm as a screening tool for the detection of retinopathy of prematurity (ROP). Participants: Images were collected from infants enrolled in the KIDROP tele-ROP screening program. Methods: We developed a deep learning (DL) algorithm with 227,326 wide-field images from multiple camera systems obtained from the KIDROP tele-ROP screening program in India over an 11year period. 37,477 temporal retina images were utilized with the dataset split into train (n= 25,982, 69.33%), validation (n=4,006, 10.69%), and an independent test set (n=7,489, 19.98%). The algorithm consists of a binary classifier that distinguishes between the presence of ROP (Stages 1-3) and the absence of ROP. The image labels were retrieved from the daily registers of the tele-ROP program. They consist of per-eye diagnoses provided by trained ROP graders based on all images captured during the screening session. Infants requiring treatment and a proportion of those not requiring urgent referral had an additional confirmatory diagnosis from an ROP specialist. Results: Of the 7,489 temporal images analyzed in the test set, 2,249 (30.0%) images showed the presence of ROP. The sensitivity and specificity to detect ROP was 91.46% (95% CI: 90.23-92.59%) and 91.22% (95% CI: 90.42-91.97%), respectively, while the positive predictive value (PPV) was 81.72% (95% CI: 80.37-83.00%), negative predictive value (NPV) was 96.14% (95% CI: 95.60-96.61%) and the AUROC was 0.970. Conclusion: The novel ROP screening algorithm demonstrated high sensitivity and specificity in detecting the presence of ROP. A prospective clinical validation in a real-world tele-ROP platform is under consideration. It has the potential to lower the number of screening sessions required to be conducted by a specialist for a high-risk preterm infant thus significantly improving workflow efficiency.